Defining the Opioid Requirement in Anterior Cruciate Ligament Reconstruction. (13th January 2022) - Sayegh, Eli T.; Otto, Tracey S.; Garvey, Kirsten D.; Martin, Anna; Lowenstein, Natalie A.; Matzkin, Elizabeth G.
Abstract : Introduction: The amount and duration of opioids necessary after anterior cruciate ligament reconstruction (ACLR) are inadequately defined. This study sought to prospectively (1) define the amount and duration of opioid consumption, (2) investigate the relationship between preoperative pain expectation and postoperative satisfaction with pain management, and (3) identify risk factors for increased opioid use after ACLR. Methods: One hundred eight patients undergoing primary ACLR with hamstring graft were prospectively analyzed for preoperative pain expectation, using visual analog scale (VAS) rating, and postoperative satisfaction with pain management. Univariate and multivariate analyses were done to identify patient characteristics associated with satisfaction and/or amount and duration of opioid use. Results: Mean duration and cumulative intake of opioid consumption after ACLR were 5.3 days and 15.3 tablets, respectively. Patients expected moderate postoperative pain: mean preoperative VAS = 68.9. The preoperative VAS rating was associated with a significantly greater amount ( P = 0.0265) and longer duration ( P = 0.0212) of opioid consumption. Baseline opioid users took opioids for twice as long postoperatively (10.0 versus 5.0 days; P = 0.0149) and consumed twice as many tablets (29.3 versus 14.8 tablets; P = 0.0280) compared with opioid-naive patients. Discussion: This study demonstrated on average 15.3 opioid tablets over 5.3 days provided satisfactory pain management after ACLR. Risk factors for increased opioid consumption included preoperative opioid use.